Legal Perspective On The Legality Of A Company Or Agency In Conducting Business - Ade Onny Siagian; Ramlani Lina Sinaulan; Joko Sriwidodo (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
In a company, it will always be connected to third parties and want to protect the company that is run honestly (